PENGARUH PERSEPSI SISWA TENTANG KOMPETENSI PEDAGOGIK DAN KOMPETENSI PROFESIONAL GURU TERHADAP HASIL BELAJAR IPS PADA SISWA KELAS VIII SMP NEGERI 1 NAN SABARIS - Putra Abdi Ramadan; surtani surtani (JURUSAN GEOGRAFI FIS UNP, 2020)
This Study aims to determine students’ perceptions about the pedagogical competence of social studies teachers in class VIII of SMP Negeri 1 Nan Sabaris in odd semester 2018/2019, then to find out students’ perceptions about the social competence of social studies teachers of class VIII SMP Negeri 1 Nan Sabaris in the odd semester of the 2018/2019 academic year and to know the learning outcomes of social studies students of the VIII grade of SMP Negeri 1 Nan Sabaris in the odd semester of the 2018/2019 school year. The type of this research is descriptive correlational, with the subject of the research is the eight grade students of SMP Negeri 1 Nan Sabaris, Padang Regency, totalling 199 people. The number of samples in this study was 83 people, the sampling technique in this study was Proportional Random Sampling technique. The research instrument to determine the effect of students’ perceptions of pedagogical competence and professional competence of teachers using a Likert Scale questionnaire and student learning outcomes data taken from the average value of odd midterm exam results. Based on the result of research and data analysis result show that : (1) The category of students’ perceptions about the pedagogical competence of social studies teachers in class VIII of SMP Negeri 1 Nan Sabaris in the January-June semester of the 2018/2019 school year based on the percentage caregory was good (79%) (2) The category of students’ perceptions of the social studies teachers of class VIII of SMP Negeri 1 Nan Sabaris in the January semester – June 2018/2019 academic year based on the percentage category was good (79%) (3) Social studies learning outcomes for class VIII od SMP Negeri 1 in the January-June semester of the 2018/2019 school year based on the percentage category is good (60.95%) Keywords : Student perceptions about pedagogical competence, professional competence of teachers and learning outcomes.